Dampak Program Sekolah 5 Hari terhadap Stres Akademik dan Efektivitas Pembelajaran Matematika Siswa SMA Negeri 1 Bosar Maligas - Fitri Anggraini; Ika Okta Kirana; Mita Sari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze the impact of the five-day school program on students’ academic stress levels and the effectiveness of mathematics learning at SMA Negeri 1 Bosar Maligas. A quantitative approach with a pretest–posttest design was employed, involving 100 students from grades XI and XII selected through stratified random sampling. The instruments used included an academic stress questionnaire with a reliability coefficient (Cronbach’s Alpha) of 0.87 and a mathematics learning effectiveness test developed based on the 2022 Independent Curriculum (Kurikulum Merdeka), with a KR-20 reliability value of 0.82. Data were analyzed using descriptive statistics, Pearson correlation, and paired sample t-test with SPSS version 26 at a significance level of ???? =0.05. The results showed an increase in the mean academic stress score from 3.08 to 3.54, indicating a decrease in students’ stress levels since higher scores represent better psychological conditions. Mathematics learning effectiveness also improved from 68.65 to 75.41. Pearson correlation analysis revealed a significant positive relationship between academic stress and learning effectiveness after program implementation (r = 0.324; p = 0.001), while the paired sample t-test indicated significant differences (p < 0.001) with large effect sizes (Cohen’s d = 1.29 and 1.44). Qualitative interviews with teachers and students revealed three adaptation phases: initial (fatigue and adjustment), intermediate (time management improvement), and stabilization (increased focus and motivation). Therefore, the five-day school program effectively reduces academic stress and enhances mathematics learning effectiveness through a gradual adaptation process among students and teachers.